Pemetaan Status Kerusakan Tanah di Lahan Pertanian di Kecamatan Cepogo Kabupaten Boyolali - Sumarno Sumarno; Sri Hartati; Ratna Cahyaning Hapsari (Universitas Sebelas Maret, 2015)
Land used in agriculture plays an important role in supporting the production of biomass. Destruction of land for biomass production is changing the nature of the soil that exceeded the standard criteria of soil damage. Mapping of land degradation status is useful to know the condition of the soil and tillage correct action. This study was conducted using a survey in the Subdistrict Cepogo Regency Boyolali. Existing data will be scoring and macthing with standard criteria for biomass production ground damage that Government Regulation No. 150 of 2000. Analysis of the data shows that there is no damage land area covering 744,1 Ha (13,7%) and there are areas relatively lightly damaged by parameters of degradation status, namely the composition of the fraction covering 494,4 ha (9,1%), the degree of release of water parameters covering 294,4 ha (5,4%) and a combination of parameters fraction composition and the degree of release of water covering 1.813 Ha (33, 4%).